Advance pricing arrangements as a tax strategy tool for related entities - Karolina Kuropka (European Financial and Accounting Journal, 2020)
The article presents the procedure of concluding an advance pricing agreement between the taxpayer and the tax authority as a tool of tax strategy of large international groups. It was pointed out that the advance pricing agreement may be a key tool to protect affiliates operating in different tax jurisdictions from the questioning of market conditions in their transactions by tax administrations. The essence and stages of concluding this agreement are presented on the basis of the tax practice applied in Poland. In addition, special attention was paid to issues concerning properly implemented tax strategy in large international capital groups. The content of the article indicates certain benefits of establishing an advance pricing arrangement and its impact on the tax strategy in a capital group.
Keywords: M21; M40; M48; 650; Tax law; Advance pricing arrangement; Related entities; Transfer prices; Tax strategy